Can AI be Evil: The Criminal Capacities of ANI - Željko Bjelajac; Aleksandar M. Filipović; Lazar Stošić (International Journal of Cognitive Research in Science, Engineering and Education, 2023)
Artificial Narrow Intelligence (ANI) represents a captivating domain within technological advancement, bearing the potential for profound societal transformations. While ANI holds the promise of enhancing various facets of human existence, it concurrently engenders inquiries into its “darker aspects.” This study delves into the challenges associated with ANI’s conceivable manifestation of harm and injustice, a phenomenon devoid of consciousness, intention, or responsibility akin to that of human entities. A pivotal dimension of ANI’s “dark side” pertains to its susceptibility to malevolent utilization. Despite its lack of awareness, ANI serves as a tool for malicious endeavors, encompassing the propagation of disinformation, compromise of security systems, and consequential decision-making. This prompts contemplation on strategies to mitigate these “precise manifestations of malevolence” arising from ANI’s technological progression. Additionally, ANI’s development introduces profound ethical quandaries. Ensuring ANI’s alignment with moral principles while averting scenarios in which it generates decisions conflicting with human morality becomes a pressing concern. This research underscores the imperative for rigorous regulatory frameworks and ethical directives to curtail potential hazards and unscrupulous utilization of ANI. The fundamental objective of this investigation is to advocate for the responsible deployment of ANI in society. A comprehensive understanding of potential risks, complemented by meticulous consideration of ethical dimensions, emerges as an indispensable prerequisite to harmonizing technological advancement with safeguarding societal and individual interests.